The Cosmetological Potential of Nelumbo Nucifera Gaertn : A Systematic Review (International Journal of Scientific Research in Science and Technology, 2025)
Nelumbo nucifera Gaertn., commonly known as the lotus, has been revered across various cultures for centuries due to its diverse applications. This systematic review aims to elucidate the cosmetologic potential of Nelumbo nucifera by examining its phytochemical composition and associated bioactivities which have been reported individually and from Lotus to be of potent use in cosmetology and cosmeceutics. The plant is rich in a variety of biochemicals, including triterpenoids, flavonoids, alkaloids, and polyphenols, which contribute to its extensive use in cosmetic and cosmeceutical products. These compounds exhibit significant range of activities such as skin whitening, antioxidant, anti-inflammatory, and anti-aging properties, making the lotus a valuable ingredient in skincare formulations.The review synthesizes current research findings to provide a scientific rationale for the traditional and contemporary uses of Nelumbo nucifera in cosmetology. It highlights the plant’s efficacy in promoting skin hydration, offering UV protection, and serving as a natural preservative. Additionally, the review explores potential new applications by providing plausible reasoning for its already reported traditional applications.By systematically analysing the existing literature, this review not only underscores the current applications of Nelumbo nucifera but also identifies promising avenues for future research. The findings suggest that the lotus holds significant potential for innovation in the cosmetic industry, driven by its rich phytochemical profile and multifaceted bioactivities. This comprehensive review thus provides a foundation for further exploration and utilization of Nelumbo nucifera in cosmetology, paving the way for new, effective, and natural cosmetic solutions.
Keywords: Nelumbo Nucifera; Lotus; Cosmetology